EFEKTIFITAS PEMANFAATAN WAKTU BELAJAR PESERTA DIDIK DI SMA NEGERI 11 PADANG - Nengsi, Deni Okto; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
The purpose ofÂ this research was to describe the effectiveness of the use of students learning time at SMA Negeri Padang as follow: 1). To describe the effectiveness of the use of learning time in students school at SMA Negeri 11 Padang, and 2). To describe the effective ness of the use of learning time in students house at SMA Negeri 11 Padang. The type of this research was descriptive research. The sample classes were X5, XI IPA1 and XII IPS1 at SMA Negeri 11 Padang. This research used purposive random sampling technique in getting the sample. The data was analyzed through percentage formula. The research result could be described as follow: 1). The effective ennes of the use of students learning time shown from the use of learning time at school was in effective enough criteria with category 67% by indicator used learning schedule at school was effective ennogh criteria, the learning time that used was in effectife enough criteria 67%, and 2). The effectiveness of the use of students learning time shown from the use of learning time at home was effective enough criteria in category 68% with indicator used learning indicator used learning schedule at home was effective enough criteria in 69% and learning time that used in effective enough criteria 66%. The researcher suggested that the studentsâ had to use theirleisure time to studyin library more effectively.